Seasonal distribution of phlebotomine sand flies (Diptera: Psychodidae) in Tham Phra Phothisat temple, Saraburi province, Thailand - R. Polseela (2018)
Phlebotomine sand flies have long been incriminated as vectors of leishmaniasis in various parts of both the Old and New World. Prompted by recent indigenous cases of leishmaniasis in Thailand, a bionomic study of sand flies was undertaken in Tham Phra Phothisat temple, Saraburi province. In this study, sand flies were collected using Centers for Disease Control (CDC) light traps, to clarify the activity patterns and species composition of the sand flies. Traps were laid from August 2005 to July 2006. The insects were collected monthly between 1800-0600 hours. A total of 8,131 sand flies were collected with a female:male ratio of 1.9:1. Sixteen species were identified, of which 5 belonged to the genus Phlebotomus, 9 to Sergentomyia and 1 to Chinius. Species comprised the abundant species (Sergentomyia silvatica 35.6%, Sergentomyia barraudi 18.1%, Sergentomyia anodontis, 17.1%, Sergentomyia iyengari 11.9%, and Sergentomyia gemmea 11.2%); the less common species ( < 2%) were Sergentomyia dentata 1.8%, Phlebotomus stantoni 1.1%, Sergentomyia indica 1.0%, Phlebotomus argentipes 0.8%, Sergentomyia perturbans 0.4%, Chinius barbazani 0.3%, Phlebotomus asperulus 0.2%, Phlebotomus philippinensis gouldi 0.1%, Phlebotomus major major 0.1%, Sergentomyia quatei 0.1% and Sergentomyia bailyi 0.1%. The results revealed seasonal variation in sand fly prevalence, with the highest peak in July. Soil samples collected were characterized by alkaline (pH 7.6).